Siglecs in allergy and asthma. (April 2023) - Bochner, Bruce S.; O'Sullivan, Jeremy A.; Chang, Alan T.; Youngblood, Bradford A.
Abstract: The term "allergic diseases" encompasses several common, IgE-mediated conditions that range from being annoying to those that are life-threatening. Available treatments include active avoidance of the instigating allergen and the use of a variety of oral, inhaled, intranasal, intraocular and injected agents. While most individuals with allergies do well with existing therapies, there are still unmet therapeutic needs. Siglecs (sialic acid-binding, immunoglobulin-like lectins) are a family of single-pass transmembrane I-type lectins found on various subsets of cells, especially those of the immune system. All Siglecs have extracellular domains recognizing sialoside ligands, and most contain cytoplasmic domains with inhibitory signaling activity. This review focuses on Siglecs that likely play a role in regulating allergic and asthmatic responses, and how specific Siglecs, expressed on cells such as eosinophils and mast cells, are being targeted for therapeutic benefit.